PENGARUH PERHATIAN ORANG TUA DAN SIKAP SOSIAL TERHADAP PRESTASI BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Suryanti dan Samsi Haryanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2014)
This study aims to determine whether there is influence of parental concern and social attitudes to learning achievement Social Sciences Elementary School fifth grade students. The population in this study were fifth grade students of elementary school of 60 students, while the sample of 50 students (5% of the total population) is determined by purposive random sampling technique according to the size of the sample with 5% significance level. Based on the results of this study concluded that: The first hypothesis reads: "There is a concern the influence of parents on the learning achievement of Social Sciences Elementary School fifth grade students, with rhitung greater than rtabel so the higher attention of the parents, the higher the student achievement. the second hypothesis states that "There is the influence of social attitudes to learning achievement of students of Social Sciences Elementary School fifth grade students. rhitung rtabel greater than the significant level of 5%, so the higher the social attitudes of students, the higher the student achievement. The third hypothesis states that "There is the influence of parental concern and social attitudes to learning achievement of students of Social Sciences Elementary School fifth grade students. Fhitung greater than the F table so that the higher the parents' attention and social attitudes of students, the higher the student achievement.